13th FINA world championships: analysis of swimsuits used by elite male swimmers - Neiva, H. P.; Vilas-Boas, J. P.; Barbosa, T. M.; Silva, A. J.; Marinho, D. A. (Journal of Human Sport & Exercise, 2011)
The purpose of this study was to describe the distribution of different swimsuits models used by male swimmers during all the finals at the 13th FINA World Championships, being held at Rome in 2009. Simultaneously, it was intended to verify the distribution of the different swimsuits used along the distances of the freestyle finals, and thus to understand the preferences of the top-level swimmers. It were used the results databases from the 13th FINA World Championships, in Rome 2009. Only the male swimmers participating at the finals were analyzed, for a total number of 17 individual swimming events. The wear swimsuit by each swimmer in a given event was observed from video recorded of the television broadcast. Male swimmers participating in the finals limited their choice to seven types of commercial swimsuits, of four different sports brands. Jaked01 Full® was the most used (47.07%), followed by the Powerskin X-Glide Full® (34.56%), the Powerskin X-Glide Pants® (7.35%) and the LZR Racer Full® (5.15%). In freestyle swimming events most of the male swimmers choose to wear full body swimsuits. Jaked01 Full® was predominant in the 50 m event, with 62.50% of swimmers choices. This value decreases to 25.00% when analyzing 100 m event, and remained similar over the longer distances swum. The Powerskin X-Glide Full® was used for 37.50% of the swimmers in 50 m swimming event, and it increases to 62.50% for the 100 m freestyle. These results seem to demonstrate that swimmers have preferences for full swimsuits, and for these two swimsuits, the Powerskin X-Glide Full® and the Jaked01 Full®.